PKM Penguatan Identitas Diri dan Karakter Pelajar SMP Negeri Hamar melalui Pendampingan Iman Berbasis Komunitas Sekolah - Aurelius Fredimento; Edwardus Dionisius Goa (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
Character formation and identity development are fundamental aspects of adolescent growth that require continuous support through faith formation. Ninth-grade students at SMP Negeri Hamar encounter various developmental challenges, including low self-confidence, poor learning discipline, limited emotional regulation skills, as well as the influences of the social environment and rapid digital technological advancement. This community service program aimed to strengthen students' character and self-identity through faith formation mentoring based on a participatory-reflective approach. The program employed several methods, including preliminary observation, interactive presentations, experiential reflection, group discussions, deepening of Christian faith values, and the formulation of personal commitments as a means of applying these values in daily life. This approach positioned students as active participants who experienced, reflected upon, and internalized faith values throughout the learning process. The findings indicate that the participants actively engaged in all mentoring activities, developed a deeper understanding of their self-identity and Christian values, demonstrated increased self-confidence and responsibility, and showed a stronger commitment to practicing positive character values within their school, family, and community environments. Therefore, participatory reflective faith formation serves as an effective strategy for fostering adolescents' character development and strengthening their self-identity in response to contemporary developmental challenges.